Analisis Simulasi Penerapan Akuntansi Sumber Daya Manusia Terhadap Perbandingan Kinerja Keuangan (Studi Kasus Pada PT Bank Pembangunan Daerah Lampung Tahun 2012-2014) - Yunus Fiscal; . Desma (Jurnal Akuntansi dan Keuangan, 2016)
Accounting provides financial information which is used by manager to make decisions. Conventional accounting (accounting which accepted generally) treats human resources costs improperly which resulted in irrelevant financial information. Human resources accounting is the answer of problems faced by manager to make decision. PT Bank Pembangunan Daerah Lampung is a company which operational activities engaged in services, which is fully aware that human resources’ dominant role as one of the main factors to support the success of the company. It’s shown from its attempt done in recruitment, selection, development, and training of the employees to support its employment candidates, yet PT Bank Pembangunan Daerah Lampung haven’t applied human resources accounting. This study purposed to analyze the financial performance with profitability ratio analysis and compare the before and after the appliance of human resources accounting simulation by experimental descriptive research method. The types of data used is secondary data from human resource costs sourced by financial statements PT Bank Pembangunan Daerah Lampung obtainable website. The result shows the financial performance of PT Bank Pembangunan Daerah Lampung gets better after human resources accounting is applied, as shows in the human resources accounting simulation. It caused cost of human resouce (acquisitions and development)  into an investment not as expense.